Reimagining the Istanbul Encampment of 2013: From Communitas to Post-Modern Sacred Openings in a Belated Modernity - Kolluoglu, Poyraz (Worldviews, 2023)
This article rests upon two kinds of deductions: first a lack of scholarly engagement within cultural constructs of religion in mainstream social movement studies; and the second, the quasi-religious aspects of occupy-like movement. These two problematics, one theoretical, and one ethnographic, are drawn together through Edith Turner’s conceptualization of communitas in light of the fieldwork findings derived from the encampment established at Istanbul’s Gezi Park in 2013.